Conectividade hidrológica em ambiente semiárido: estudo de caso bacia hidrográfica do açude Orós - Toledo, Cristian Epifânio de (2013)
Attempting to solve the drought problem, political decisions prioritized the construction of reservoirs, what eventually resulted in the construction of a "high density network of reservoirs" in the Brazilian Northeast. Usually, a reservoir interrupts the natural river flow, thus interfering in the water dynamics downstream. This work was aimed at studying the processes involved in the hydrological connectivity as well as the interference of multiple reservoirs in the hydrologic network connectivity of a large semiarid basin. The case study is the catchment area of the Orós - BHAO (24,211 km2 ) reservoir, located in Semiarid Ceará. The research began with a survey of the BHAO dense reservoir network topology, conducted using remote sensing (RS), GIS tools (GIS) and satellite image at the end of the 2011 rainy season. The hydrological connectivity analysis was performed using the 'Reservoir Network Model' (ResNetM), which simulated hydrologic processes and considered the hydrological connectivity between the reservoirs, according to the criteria established in this research model. While seeking to identify the key natural and anthropogenic factors affecting the hydrological connectivity of the basin, an analysis of input sensitivity (IS) of some input parameters of the model was performed, this allowed us to evaluate the reservoir network impact on the stored volume on the Orós reservoir. The survey of the network of reservoirs with SR and automatic GIS tools showed two shortcomings: the misinterpretation of shadows as reservoirs and the misidentification of the actual water surface due to the macrophyte presence in reservoirs. Thus, of the 6,002 automatically generated polygons, only 4717 polygons (79%) were confirmed as reservoirs, after manual adjustment. The survey found that in the last decade, there was a 17.5% increase in the number of BHAO reservoirs and that, in regions with crystalline geology, the density of reservoirs is 80% higher than in regions of sedimentary geology. The sensitivity analysis indicated that the number of reservoirs in the network was the variable to which the system showed higher sensitivity (SI = 1.07), considering the hydrological connectivity. In contrast, the evaporation variation (SI = 0.19) and loss in transit (SI = 0.01) did not induce significant changes on BHAO hydrological connectivity. Also, the volume stored in the Orós reservoir showed no significant changes (SI = 0.21) when the reservoir network topology was modified. For example, when the removal of small and medium network reservoirs (4,664, or 98.9% of the reservoirs) was simulated, the Orós reservoir indicated an increase of only 14% in its average volume stored. Based on observations, it was concluded that there was a reduction in the rate of annual BHAO reservoir increment in the past 10 years, marking the beginning of the stabilization phase of the said network. Among the evaluated natural elements, it was the (natural) runoff coefficient which was demonstrated to have the most significance for the hydrological connectivity. Its importance is due to the fact that in the BHAO natural system, underground flow is infrequent. Of the human elements analyzed, the dense reservoir network, obtained the highest importance for hydrological connectivity. The reason for this is that the reservoirs promote the lamination of the flood wave, increasing the number of days with river flow and, consequently, increase the frequency of hydrological connectivity. In addition, new reservoirs decrease the length of the passages to be connected, reducing losses in transit and promoting hydrological connectivity. The variation of the reservoir network demonstrated that decreasing the number of network reservoirs, a decrease in BHAO hydrological connectivity occurs, not changing, however, significantly the inflow to the Orós reservoir, the convergence focus of the network. A dense reservoir network showed that, at the beginning of the rainy season, it acts as a barrier to river flow, breaking hydrological connectivity. Over time and with continued rainfall, the thousands of reservoirs promote hydrological connectivity by lamination of the flood wave.